Maternal and infant factors that shape neonatal gut colonization by bacteria. (2nd August 2020) - O'Neill, Ian J.; Sanchez Gallardo, Rocio; Saldova, Radka; Murphy, Eileen F.; Cotter, Paul D.; McAuliffe, Fionnuala M.; van Sinderen, Douwe
ABSTRACT: Introduction: Early life is a critical developmental window coinciding with the establishment of a community of neonatal gut microbes which are vitally important for immune development. The composition of this microbial community is affected by multiple factors. Areas covered: The effect of pre-pregnancy and pregnancy maternal health, maternal nutrition, pregnancy disorders such as gestational diabetes, maternal antibiotic usage, delivery mode, infant feeding, and infant antibiotic usage on gut microbial composition are outlined along with the potential impact of associated microbiota differences on infant health. Expert opinion: Recent developments in understanding what shapes our microbiota indicates that the greatest impact on infant gut microbiota composition during the first year of life is seen with the mode of delivery, infant diet, and infant antibiotic usage. Current data is insufficient to fully establish the role of apparently less important factors such as maternal health on microbiota development although their impact is likely smaller. Technological advances will allow for improved understanding of underlying mechanisms by which specific microbes impact on infant health, which in time will enable full appreciation of the role of the gut microbiota in early life development.